Rock & roll highway : the Robbie Robertson story - Robertson, Sebastian (Christy Ottaviano Books, Henry Holt and Company, 2014)
"Canadian guitarist and songwriter Robbie Robertson is known mainly for his central role in the musical group the Band. But how did he become one of Rolling Stone's top 100 guitarists of all time? Written by his son Sebastian, this is the story of a rock-and-roll legend's journey through music, beginning when he was taught to play guitar at nine years old on a Native American reservation"--Amazon.com.